Association between quality of life and handgrip strength among malnourished gynaecological cancer outpatients, National Cancer Institute - Mohammad, Aini Masitah; Abu Zaid, Zalina; Ho, Chiou Yi; Ibrahim, Zuriati; Mat Daud, Zulfitri 'Azuan; Md. Yusop, Nor Baizura; Jamhuri, Norshariza; Abd Rahman, Zuwariah (Persatuan Pemakanan Malaysia, 2020)
Introduction: Malnutrition is common among cancer patients and it is reported in a significant proportion of patients with gynaecological cancer (GC). The aim of this study was to determine the association between quality of life (QOL) and hand grip strength (HGS) among malnourished GC outpatients in the National Cancer Institute (NCI). Methods: This study was carried out in a Multidisciplinary Clinic of NCI. HGS was measured using Jamar Hand Dynamometer. Nutritional status was assessed using the scored Patient-Generated Subjective Global Assessment (PGSGA). QOL was measured using the validated European Organisation for Research and Treatment of Cancer Questionnaire (EORTC-QLQ C30). Results: A total of 69 patients were selected for the study. Fifty eight (84.1%) were classified as moderately malnourished or at risk of malnutrition (PG-SGA B) and 11 (15.9%) were classified as severely malnourished (PG-SGA C). There was a moderate, significant positive relationship between HGS and functional status (rs=0.275, p=0.022) observed in this study. Besides, in malnourished GC patients with low HGS, results indicated that they had problems with social functioning as well (r=0.255, p=0.035). Appetite was suggested as a predicting factor for low HGS among malnourished GC patients (F=12.253, p=0.001). Conclusion: HGS is a simple objective indicator of functionality and is, therefore, a valid item to be measured when assessing QOL of malnourished GC outpatients.